Influenza vaccine compatibility among hospitalized patients during and after the COVID-19 pandemic - Fratty, Ilana S.; Jurkowicz, Menucha; Zuckerman, Neta; Nemet, Ital; Atari, Nofar; Kliker, Limor; Gur-Arie, Lea; Rosenberg, Alina; Glatman-Freedman, Aharona; Lustig, Yaniv; Mandelboim, Michal (Frontiers in Microbiology, 2024)
Following the significant decrease in SARS-CoV-2 cases worldwide, Israel, as well as other countries, have again been faced with a rise in seasonal influenza. This study compared the circulating influenza A and B in hospitalized patients in Israel with the influenza strains in the vaccine following the 2021-2022 winter season which was dominated by the omicron variant. Of the 16,325 nasopharyngeal samples collected from hospitalized patients between September 2021 (Week 40) and April 2023 (Week 15), 7.5% were found to be positive for influenza. The hemagglutinin (HA) protein of 77 samples was sequenced using the Sanger method and phylogenetic analysis was conducted. In the 2021-2022 winter season, the leading virus subtype was influenza A(H3N2), which belongs to clade 3C.2a1b.2a.2. However, the following winter season was dominated by influenza A(H1N1)pdm09, which belongs to clade 6B.aA.5a.2. The circulating influenza A(H1N1)pdm09 strain showed a shift from the vaccine strain, while the co-circulating influenza A(H3N2) and influenza B strains were similar to those of the vaccine. Influenza prevalence during 2022-2023 returned to typical levels as seen prior to the emergence of SARS-CoV-2, which may suggest a gradual viral adaptation to SARS-CoV-2 variants.